FAKTOR – FAKTOR YANG MEMPENGARUHI KEPATUHAN PAJAK BUMI DAN BANGUNAN (P-2) (Studi pada WPOP di Kabupaten Klaten) - Riana Widiastuti; Herry Laksito (Diponegoro Journal of Accounting, 2014)
The purpose of this study was to investigate variables behave attitude, subjective norm, perceived behavioral control, awareness, knowledge of sanctions and services tax on taxpayer compliance behavior on Land and Building Tax in Klaten district.Respondents used in the study was an individual taxpayer in the district Klaten. Furthermore, sampling method to collect data was from 100 respondents to apply the method of purposive sampling. Multiple linear regression analysis was used to analyze research data.The test results in the study show that attitudes behave, subjective norms, perceived behavioral control, consciousness, service tax affect taxpayer behavior to obey to taxation. While knowledge of tax penalties do not affect taxpayer behavior to obey to taxation. This is because only provides insight and knowledge of the general picture that is not quite create a positive perception of taxpayers to comply with tax regulations. Furthermore, the perception created by the taxpayer is not influenced by knowledge of the tax penalties are owned by the taxpayer.